Penerapan Standar Kompetensi Lulusan Mata Pelajaran Bahasa Indonesia Sekolah Dasar - Sevtivia Asrivi, Queen Elvina; Rokhman, Fathur; Deliana, Sri Maryati (Journal of Primary Education, 2017)
Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis hambatan dalam pelaksanaan Standar Kompetensi Lulusan (SKL) yang dibuat guru kelas VI mata pelajaran Bahasa Indonesia SD di Kecamatan Slawi. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik analisis data model interaktif yaitu pengumpulan data (data collection), reduksi data (data reduction), penyajian data (display data), dan verifikasi (conclusion drawing). Dalam penelitian ini menggunakan delapan partisipan penelitian yang terdiri dari empat kepala sekolah dan empat guru kelas VI. Hasil penelitian penerapan Standar Kompetensi Lulusan (SKL) disusun melalui tiga tahapan yaitu (1) tahap persiapan yang terdiri atas (a) Memiliki kelengkapan dokumen Prosedur Operasional Standar Ujian Sekolah/Madrasah (POS US/M), (b) Melaksanakan tambahan jam. (2) Tahap pelaksanaan terdiri dari (a) Menganalisis hasil try out, (b) Merancang nilai SKL Bahasa Indonesia, (c) Musyawarah dengan nilai SKL Bahasa Indonesia dengan stakeholder pendidikan. Tahap yang terakhir yaitu (3) tahap evaluasi atas ketercapaian SKL Bahasa Indonesia. Hambatan dalam penyusunan berasal dari siswa, guru dan orang tua dalam penyusunan SKL diantaranya kemampuan siswa yang rendah,pelaksanaan tambahan jam yang tidak sesuai dengan jadwal, musyawarah penentuan SKL dan pembelajaran Bahasa Indonesia belum optimal. Berdasarkan hasil tersebut dapat disimpulkan penyusunan SKL mata pelajaran Bahasa Indonesia berjalan sesuai dengan POS US/M SD dan siswa mampu mencapai SKL yang sudah ditentukan.This study aims to describe and analyze the obstacles in the implementation of graduate competency Standards which made the sixth grade teacher of Indonesian Language subject elementary school in Slawi district. The research used descriptive qualitative approach with interactive data analysis technique that is data collection, data reduction, presentation data, and conclusion drawing. In this study using eight study participants consisting of four principals and teachers of class sixth. The results of this study that the application of graduate competency standards is (1) Prepared through three steps of preparation stage consisting of Indonesian Language subject (a) Having the completeness of Document of standard operational procedure for school exam (POS US/M) documents, (2) Implement additional hours. Implementation phase consists of (a) Analyzing try out results, (b) Designing Graduate Competency Standards score of Indonesian Language subject, (c) Deliberation with graduate competency standards score of with education stakeholder. The final stage is (3) The evaluation stage of Indonesian graduate competency standards achievement. Obstacles in the preparation comes from students, teachers and parents in the preparation of graduate competency standards including low student ability, the implementation of additional hours that are not in accordance with the schedule, deliberation determination Graduate competency standards and learning Indonesian subject is not optimal. Based on these results it can be concluded that the preparation of graduate competency Standards Indonesian subjects run in accordance with the POS US/M documents and students are able to reach the graduate competency standards that has been determined.